2022
DOI: 10.3390/plants11223128
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Some Methoxyflavones Extracted from Rhizome of Kaempferia parviflora Combined with Gentamicin against Carbapenem-Resistant Strains of Klebsiella pneumoniae, Pseudomonas aeruginosa, and Acinetobacter baumannii

Abstract: The present study aimed to investigate the antibacterial activity of ethanolic Kaempferia parviflora extracts and the combined effects of the plant’s specific compounds with gentamicin against clinical strains of carbapenem-resistant Klebsiella pneumoniae, Pseudomonas aeruginosa, and Acinetobacter baumannii. The minimal inhibitory concentrations (MIC) of gentamicin and Kaempferia parviflora extracts against the tested bacterial strains were determined by using broth microdilution. The combined effects of Kaemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Both effects might very well accelerate wound healing. The methoxyflavones found in the ethanolic KP extract enhanced the antibacterial activity of gentamicin to combat bacterial resistance against P. aeruginosa , Klebsiella pneumoniae , and Acinetobacter baumannii strains resistant to carbapenems [ 57 ]. Therefore, KP extract should be combined with antibiotics to create electrospun shellac fibers for more efficient wound healing.…”
Section: Resultsmentioning
confidence: 99%
“…Both effects might very well accelerate wound healing. The methoxyflavones found in the ethanolic KP extract enhanced the antibacterial activity of gentamicin to combat bacterial resistance against P. aeruginosa , Klebsiella pneumoniae , and Acinetobacter baumannii strains resistant to carbapenems [ 57 ]. Therefore, KP extract should be combined with antibiotics to create electrospun shellac fibers for more efficient wound healing.…”
Section: Resultsmentioning
confidence: 99%
“…A concrete conclusion regarding the mechanisms responsible for the synergic activity of natural products together with antibiotics cannot be obtained [161][162][163][164]. Some authors have suggested that synergic effects could be observed due to changes in the efflux system, damage to cell membranes, and the inhibition of protein synthesis.…”
Section: Gentamicin Combinations With Natural Productsmentioning
confidence: 99%
“…Some authors have suggested that synergic effects could be observed due to changes in the efflux system, damage to cell membranes, and the inhibition of protein synthesis. Further research is needed to clearly understand the mechanisms [161,162,164]. A study using propolis revealed that the concentration of natural products is also crucial to the synergic activity [161].…”
Section: Gentamicin Combinations With Natural Productsmentioning
confidence: 99%
“…The standard checkerboard assays were performed as described previously to evaluate the combination effect of each tested lactic acid bacteria and the plant extracts against C. albicans ATCC10231 [29]. Fifty microliters of LM supernatant dissolved in MRS broth was serially diluted with MRS broth along the vertical axis of rows 1st-7th (top and bottom: the highest and lowest final concentrations were performed in titers at 1 and 7, respectively).…”
Section: Fractional Inhibitory Concentration Index Of Anticandidal Ac...mentioning
confidence: 99%
“…All experiments were performed in triplicate. The Fractional Inhibitory Concentration Index (FICI) value was used to assess whether synergism, indifference, or antagonism occurred following the combination effects of LM and PM employing the following formula [29]:…”
Section: Fractional Inhibitory Concentration Index Of Anticandidal Ac...mentioning
confidence: 99%